Sacubitril/Valsartan contributes to improving the diabetic kidney disease and regulating the gut microbiota in mice - Wang, Peipei; Guo, Ruixue; Bai, Xiwen; Cui, Wen; Zhang, Yiding; Li, Huangmin; Shang, Jin; Zhao, Zhanzheng (Frontiers in Endocrinology, 2022)
Background Diabetic kidney disease (DKD), as a serious microvascular complication of diabetes, has limted treatment options. It is reported that the Sacubitril/Valsartan (Sac/Val) can improve kidney function, and the disordered gut microbiota and part of its metabolites are related to the development of DKD. Therefore, we aim to explore whether the effect of Sac/Val on DKD is associated with the gut microbiota and related plasma metabolic profiles. Methods Male C57BL/6J mice were randomly divided into 3 groups: Con group (n = 5), DKD group (n = 6), and Sac/Val group (n = 6) . Sac/Val group was treated with Sac/Val solution. The intervention was given once every 2 days for 6 weeks. We measured the blood glucose and urine protein level of mice at different times. We then collected samples at the end of experiment for the 16s rRNA gene sequencing analysis and the untargeted plasma metabonomic analysis. Results We found that the plasma creatinine concentration of DKD-group mice was significantly higher than that of Con-group mice, whereas it was reduced after the Sac/Val treatment. Compared with DKD mice, Sac/Val treatment could decrease the expression of indicators related to EndMT and renal fibrosis like vimentin, collagen IV and fibronectin in kidney. According to the criteria of LDA ≥ 2.5 and p<0.05, LefSe analysis of gut microbiota identified 13 biomarkers in Con group, and 33 biomarkers in DKD group, mainly including Prevotella, Escherichia_Shigella and Christensenellaceae_R_7_group, etc. For the Sac/Val group, there were 21 biomarkers, such as Bacteroides, Rikenellaceae_RC9_gut_group, Parabacteroides, Lactobacillus, etc. Plasma metabolomics analysis identified a total of 648 metabolites, and 167 important differential metabolites were screened among groups. KEGG pathway of tryptophan metabolism: M and bile secretion: OS had the highest significance of enrichment. Conclusions Sac/Val improves the renal function of DKD mice by inhibiting renal fibrosis. This drug can also regulate gut microbiota in DKD mice.